A first step in developing a DSS for responding to the detonation of an IND. Issue 4 (1st October 2016) - Jefferson, Theresa; Harrald, John R.
Abstract: Terrorist attacks cause immediate devastation that is further compounded by the confusion following the event. The physical and social loss resulting from the detonation of an improvised nuclear device (IND) would be extreme. The lack of a coordinated and informed response to such an event would be catastrophic. However, through the use of informed planning and preparedness, impacts to an IND could be mitigated. Planning for such events has been limited due to an inability to quantify impacts to the human and built environment. This research develops a model that can be used to estimate the social impacts associated with the detonation of an IND. Using these estimates, it is possible to begin to estimate the required response capability and capacity. This study also identifies the information requirements necessary to develop a decision support system that could be used in planning for the explosion of an IND.